Contribution of Fault Geometry on Probabilistic Seismic Hazard Assessment in Intermontane Basin: An example from Kathmandu Valley (Journal of Nepal Geological Society, 2020)
The intermontane basins of the Himalaya are prone to damaging earthquakes as they are located roughly 10-15 km above the Main Himalayan Thrust (MHT), a major seismogenic thrust fault in the Himalaya.  After the Mw 7.8 2015 Gorkha earthquake, the geometry of the MHT has been investigated using different approaches. Two contrasting models with a single ramp and double ramp geometries are proposed. However, the contribution of these geometries on seismic hazard has not been investigated yet. In this contribution, therefore, a probabilistic seismic hazard assessment is carried out using both models for Kathmandu valley and the obtained results are compared with the measured strong ground motion data of main shock of the 2015 Gorkha seismic sequence at Kirtipur, Kathmandu (rock site). It is found that the areal sources have the least contribution indicating sole contribution of MHT to relatively higher level of seismic hazard in the valley located on the up-dip locked portion of the MHT. The Peak Ground Acceleration (PGA) of the main shock of the 2015 Gorkha earthquake and PGA for 760 yr (exposure period of 50 yr and probability of exceedance 6.36%) of return period adopting both single and double ramp models are approximately same with error level of ± 3.84%. The results indicate that the adopted seismic model fairly represents the seismo-tectonic of the region, particularly of MHT. Considering this as the best fit results, the spatial distribution of the seismic hazard is analysed using double ramp model. It is found that the PGA values in the valley for 760 yr return period vary from 0.24 g to 0.28 g. The PGA values are higher in the southern part and gradually decrease towards north. Such decrease in PGA is consistent with the decrease in locking level of the MHT towards north. The study, therefore, emphasizes detailed geometrical characterization of the MHT while carrying out the seismic hazard assessment in the Himalaya.